Functions of the Addresses in the Story by F. Iskander “Harlampo and Despina” (Proceedings of Southern Federal University. Philology, 2020)
The article is devoted to the analysis of the use of addresses in the story of F. Iskander «Harlampo and Despina». We define their functions (appealvocative, focusing, interpersonal, illocutional, segmentation), role in creating speech portraits of characters, graphic design (syllabication, punctuation marks) and author’s comment of their use related to the implementation of narrative strategy with a pragmatically motivated narrator.Key words: F. Iskander, «Harlampo and Despina», functions of addresses.DOI 10.18522/1995-0640-2020-2-122-130